Stationary temperatures in a hollow cylinder with variable thermic conductivity using a Hankel transform - Villalobos, Alfredo (Rev. Téc. Fac. Ing. Univ. Zulia)
In the present work the Hankel generalized finite transform of third class is used to determinate the stationary temperature distribution u(r, z) in a hollow cylinder with variable thermic conductivity.